1998
DOI: 10.1111/j.1398-9995.1998.tb04087.x
|View full text |Cite
|
Sign up to set email alerts
|

Guanine, mite, and cockroach allergens in Costa Rican homes

Abstract: Previous studies of schoolchildren in Costa Rica have shown an asthma prevalence of 23% and a high level of sensitization, particularly to mite allergens. As a continuation of these studies, some 400 dust samples were collected from various places in Costa Rica, and parts of these were analyzed for specific mite and cockroach allergens, as well as for the number of mites and amount of guanine. Guanine was quantified by a diazo, as well as an HPLC method, which were found to be highly correlated. The concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…Allergy to cockroaches was first reported in 1964 by Bernton & Brown in New York (36), who showed that 40% of their asthmatic patients were sensitive to cockroaches. Since that time, many studies have shown that among exposed populations in the United States, China, Costa Rica, Hong Kong, Malaysia, Taiwan, Japan, and Europe, the sensitivity to cockroaches ranges from 23-60% (45,88,126,127,159,160,179,227,238,240,280). Among patients with atopic rhinitis, atopic dermatitis, and asthma, the prevalence of sensitivity to cockroach allergens in Italy, France, and Brazil is reported to be 12.5, 24.5, and 55%, respectively (37, 201, 223).…”
Section: Cockroachesmentioning
confidence: 99%
“…Allergy to cockroaches was first reported in 1964 by Bernton & Brown in New York (36), who showed that 40% of their asthmatic patients were sensitive to cockroaches. Since that time, many studies have shown that among exposed populations in the United States, China, Costa Rica, Hong Kong, Malaysia, Taiwan, Japan, and Europe, the sensitivity to cockroaches ranges from 23-60% (45,88,126,127,159,160,179,227,238,240,280). Among patients with atopic rhinitis, atopic dermatitis, and asthma, the prevalence of sensitivity to cockroach allergens in Italy, France, and Brazil is reported to be 12.5, 24.5, and 55%, respectively (37, 201, 223).…”
Section: Cockroachesmentioning
confidence: 99%
“…Data from South America [34][35][36][37][38][39][40], the Caribbean [41,42], and Southeast Asia [43][44][45] show that D. pteronyssinus and Blomia tropicalis are the predominant species, but D. farinae is present in low numbers. A survey of 41 dwellings in Upper Silesia, Poland [46], found most to be infested with both D. farinae and D. pteronyssinus.…”
Section: Mites and Allergen Found In Homesmentioning
confidence: 99%
“…In our study, the prevalence of rhinitis was reported to be higher during the rainy season, from May to October, probably due to high humidity, causing high mite and cockroach concentrations in homes, especially in the beds (16), as well as the presence of an usually rich variety of pollens and molds in Costa Rica, at that time of the year. Viral infections increase in prevalence during the rainy season and possibly the asthmatic and rhinitic symptoms are related to them.…”
Section: Discussionmentioning
confidence: 79%
“…The most prevalent IgE antibodies were directed against the mite Dermatophagoides farinae, cockroach, dog, and housedust allergens. 16 In a previous investigation of Costa Rican schoolchildren, aged 5-17 years, we found that allergic rhinitis was present in 32.8% and atopic dermatitis in 14.2% of the children with asthma, as compared with 17.3% and 12.9% of the nonasthmatics. 24 SOTO-QUIRÓS ET AL.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation